2020
DOI: 10.1111/dth.13362
|View full text |Cite
|
Sign up to set email alerts
|

Remodeling of collagen constituting interlobular septa of subcutaneous adipose tissue following microwaves application

Abstract: In this study, the application of a recently introduced device based on electromagnetic energy transfer by microwaves for fat reduction, permitted to study specifically the modifications of thick fibrous collagen interlobular septa in the subcutaneous adipose tissue, related to the formation of large clusters of adipocytes. The use of Picrosirius red staining associated with circularly polarized microscopy gave evidence of appreciable modifications of the fibrous connective tissue forming septa. Compact fibrot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
13
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 15 publications
0
13
0
1
Order By: Relevance
“…Microwaves can directly heat collagen septa, leading to a dissolution of deepest collagen fibers and activating fibroblasts, improving skin texture. 25 These processes could activate macrophages which, by remov-…”
Section: Discussionmentioning
confidence: 99%
“…Microwaves can directly heat collagen septa, leading to a dissolution of deepest collagen fibers and activating fibroblasts, improving skin texture. 25 These processes could activate macrophages which, by remov-…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, it was already demonstrated in the study of Zerbinati and colleagues [14] that treatment with ONDA is effective for cellulite through the remodeling of collagen and for skin laxity, with a good tightening of collagen: data have shown that Picrosirius red staining in association with circularly polarized microscopy has had evidence of appreciable changes in the fibrous connective tissue forming the septa. It has been observed that there is a reorganization of the connective tissue; the MMPs (metal proteases, lytic enzymes) digest the old collagen (collagen I), and the fibroblasts, stimulated by this denatured collagen, begin to synthesize new collagen (collagen III), which is more elastic and contributes to the reduction in the orange peel aspect of cellulite.…”
Section: Introductionmentioning
confidence: 98%
“…The effect is the loss of the pockmarked appearance of the skin but also a reactivation of the fibroblasts to produce new collagen. Finally, on skin laxity, the heat produced by the microwaves, even rising from the subcutis, causes immediate shrinking (contraction) of the collagen in the dermis, inducing a consequent tightening (tension) [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…In a recent study by Zerbinati et al, 22 authors tried to evaluate the structural modifications of collagen fibers of interlobular septa in vietnamese pigs, after microwaves treatment. Subcutaneous adipose tissue samples stained with Picrosirius red, a dye which not only stains specifically collagen fibers, but also enhances the collagen optical birefringence, demonstrated that compacted collagen fibers constituting fibrotic septa undergo to fragmentation and remodeling, starting few hours following microwaves treatment.…”
Section: Discussionmentioning
confidence: 99%
“…These processes could activate macrophage, responsible Abdomen pictures of a 36-y-old female patient before (A-C) and 8 weeks after (B-D) the combined microwaves and fractional microablative CO2 laser treatment of adipocytes, thus resulting in reduction of subdermal fatty tissue and reduction in circumference. 12In a recent study by Zerbinati et al,22 authors tried to evaluate the structural modifications of collagen fibers of interlobular septa in vietnamese pigs, after microwaves treatment. Subcutaneous adipose tissue samples stained with Picrosirius red, a dye which not only stains specifically collagen fibers, but also enhances the collagen optical birefringence, demonstrated that compacted collagen fibers constituting fibrotic septa undergo to fragmentation and remodeling, starting few hours following microwaves treatment.…”
mentioning
confidence: 99%